Experimental study on quality of PCD tools machined by different electric discharge grinding processes. Issue 1 (31st December 2016) - Li, Guangxian; Rahim, Mohammad Zulafif; Ding, Songlin; Sun, Shoujin; Mo, John
Abstract: Polycrystalline diamond (PCD) is a promising tool material which is utilized to cut difficult-to-machine materials used in aerospace industry. Because of its ultra-hardness, electrical discharge grinding (EDG), a variation of electrical discharge machining, is often adopted to manufacture PCD tools to reduce manufacturing time. This paper investigates the quality of PCD inserts manufactured by two different EDG eroding methods: "2-step machining" and "3-step machining". Surface roughness and residual stress were investigated after EDG process. An orthogonal cutting experiment was conducted to test the performance of each PCD insert. PCD tools machined with the two methods do not have significant difference in surface roughness. The residual stress status changed from compressive to tensile after EDG process. Also, after being eroded by 3-step EDG process, there was an over 30% declination of residual stress compared with 2-step machining. The results of the orthogonal cutting test showed that the wear amount and the thrust force of PCD inserts machined by 3-step EDG were smaller for the CTB010 insert and the CTX002 insert. In contrast, the CTM302 machined by 3-step EDG did not show obvious improvement in tool wear resistance during the cutting tests.